2017
DOI: 10.1111/nep.12957
|View full text |Cite
|
Sign up to set email alerts
|

Roles of tumour necrosis factor‐related weak inducer of apoptosis/fibroblast growth factor‐inducible 14 pathway in lupus nephritis

Abstract: KEY WORDS:fibroblast growth factor-inducible 14, glomerular basement membrane, lupus nephritis, proinflammatory cytokines, tumour necrosis factor-related weak inducer of apoptosis. Correspondence SUMMARY AT A GLANCEThis review describes evidence supporting a pathogenic role for tumour necrosis factorrelated weak inducer of apoptosis (TWEAK) in human and experimental lupus nephritis. Current understanding of TWEAK is integrated with known mechanisms of renal inflammation and fibrosis. This is highly relevant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…TWEAK engages its sole receptor fibroblast growth factor-inducible 14 (Fn14) and modulates various cell types under inflammatory condition (1012). TWEAK/Fn14 interaction plays an important role in the pathogenesis of tissue injuries in systemic lupus erythematosus, including lupus nephritis (13), neuropsychiatric disease (14), and cardiovascular disease (15). Besides, the TWEAK/Fn14 pathway is activated in skin lesions of MRL/lpr lupus-prone mice (16), and Fn14 deficiency protects these mice from CLE inflammation induced by UVB irradiation (17).…”
Section: Introductionmentioning
confidence: 99%
“…TWEAK engages its sole receptor fibroblast growth factor-inducible 14 (Fn14) and modulates various cell types under inflammatory condition (1012). TWEAK/Fn14 interaction plays an important role in the pathogenesis of tissue injuries in systemic lupus erythematosus, including lupus nephritis (13), neuropsychiatric disease (14), and cardiovascular disease (15). Besides, the TWEAK/Fn14 pathway is activated in skin lesions of MRL/lpr lupus-prone mice (16), and Fn14 deficiency protects these mice from CLE inflammation induced by UVB irradiation (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although LN is classified into Class I to Class VI according to pathological patterns (2), renal fibrosis is definitely the common final outcome at the end stage (1). The fibrotic lesions are associated strongly with poor outcome of patients with LN (3). During the progression of renal fibrosis, profibrotic cytokines are continuously released, and consequently enhance the phenotype changes of resident cells as well as the accumulation of extracellular matrix (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…The fibrotic lesions are associated strongly with poor outcome of patients with LN (3). During the progression of renal fibrosis, profibrotic cytokines are continuously released, and consequently enhance the phenotype changes of resident cells as well as the accumulation of extracellular matrix (3, 4). Therefore, elucidation of the pathogenesis of renal fibrosis, especially the regulation of profibrotic cytokines, is important in the development of therapeutic strategies for patients with LN.…”
Section: Introductionmentioning
confidence: 99%
“…TWEAK is a significant proinflammatory cytokine in vitro and in vivo [20]. TWEAK/Fn14 interaction has been shown to mediate diverse bioactivities involving the activation of cell proliferation, migration, or apoptosis; the induction of vasculitis and angiogenesis; the production of inflammatory cytokines; and the promotion of fibrogenic responses [15, 20]. In in vitro experiments, TWEAK has been found to induce the production of multiple cytokines, including regulated on activation, normal T-cell expressed and secreted (RANTES), monocyte chemoattractant protein-1 (MCP-1), interferon-γ–induced protein 10 (IP-10), macrophage inflammatory protein-1 alpha (MIP-1α), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) [14, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing evidence has indicated that the TWEAK/Fn14 signaling pathway plays a pivotal role in the pathogenesis of lupus erythematosus, which presents cutaneous, renal, and neuropsychiatric diseases [15-17]. Moreover, the TWEAK/Fn14 signals participate in the development of various dermatoses, such as psoriasis [7], atopic dermatitis [8], cutaneous vasculitis [18], human papillomavirus (HPV) infection [9], and bullous pemphigoid [10].…”
Section: Introductionmentioning
confidence: 99%